Counseling to Pregnant Women about Danger Signs Pregnancy in Preparation Childbirth in Aek Haruaya Village Subdistrict Portib North Padang Lawas Regency - Riska Yanti Harahap; Harahap, Ica Fauziah; Ramadhani Nainggolan; Melia Shintia Mutiara Pohan (PT Inovasi Pratama Internasional, 2024)
His height Number death Mother in Indonesia caused by a number of factor health and non-health, for example there are still many births assisted by witch doctor baby or caused by disease or problem nutrition. The maternal mortality rate (MMR) is one indicator of maternal health in Indonesia Still tall when compared to with country ASEAN. Knowledge about the danger signs of pregnancy is very important for mothers to know pregnant if found sign danger pregnancy can quick Possible request help to power health. The aim of this community service is as a form of the tri dharma of higher education and also to increase the knowledge of pregnant women about the danger signs of pregnancy in Aek Haruaya Village, Portibi District, North Padang Lawas Regency. This community service was carried out on January 8 2024 and the implementation went well with the number of participants being 25 pregnant women. It is hoped that after carrying out this activity it can increase pregnant women's knowledge about the signs and dangers that can occur during pregnancy.